Low-temperature copper paste capable of being sintered in atmospheric environment and preparation method of low-temperature copper paste
By using dispersant materials in low-temperature copper slurry to replace reducing agents and additives, the oxidation and toxicity problems of low-temperature copper slurry when sintered in atmospheric environments are solved, and the effects of improved conductivity, cost reduction and green production are achieved.
Patent Information
- Application Number
- CN202411722527.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-28
AI Technical Summary
The existing low-temperature copper slurry has oxidation problems when sintered in atmospheric environments, resulting in an increase in resistance, and the reducing agents and additives used are toxic and explosive, affecting environmental and personal safety.
By reducing the use of reducing agents and additives, dispersant materials are used to achieve the role of reducing agents and additives at the same time. The dispersant uses organic materials with functional groups containing amino and amide groups to coat copper particles, prevent agglomeration, and reduce oxidized copper powder and copper wires through photothermal decomposition during photon sintering.
The conductivity of low-temperature copper slurry sintered in atmospheric environment is improved, the preparation cost is reduced, the process is simplified, and all raw materials are non-toxic and harmless, meeting the requirements of green production.
Smart Images

Figure CN119724682A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of flexible electronics, and in particular to a low-temperature copper paste that can be sintered in an atmospheric environment. Background Art
[0002] Flexible electronic paste is one of the important materials in flexible electronic components and is widely used in flexible display screens, flexible electrodes, flexible heating devices and other devices. As the most mature product in the application of flexible electronic paste, low-temperature silver paste has the disadvantages of high cost and easy electromigration, which limits the sustainable development of low-temperature silver paste.
[0003] Low-temperature copper paste has the characteristics of low cost, large copper reserve and conductivity similar to silver, and has been proven to be one of the most promising materials to replace low-temperature silver paste. However, there are still many problems with the low-temperature copper paste prepared domestically. The formula mentioned in the invention patent "A copper paste, copper circuit, flexible electronic device and photovoltaic heterojunction battery" (CN 117497223A) contains glass binder, which cannot be sintered below 200°C, resulting in the destruction of the flexible substrate. On the other hand, the reducing agents used include hydrazine hydrate, NaBH4 and other toxic and explosive materials, which have adverse effects on the environment and personal safety; although the invention patent "Photon sintering conductive copper paste and its preparation method, antenna and RFID tag" (CN 118098674A) involves atmospheric sintering conductive copper paste, the nano-scale copper powder used is not combined with a practical coating agent or reducing agent, which is very easy to oxidize during the atmospheric sintering process, resulting in an increase in resistance; the invention patent "A method for preparing a conductive copper paste capable of photon sintering" (CN 115642000B) does not contain a dispersant, which will make it difficult to effectively disperse the nano-copper powder used during the grinding stage, causing agglomeration and resulting in a decrease in resistance. Summary of the invention
[0004] The object of the present invention is to provide a low-temperature copper paste which can be sintered in an atmospheric environment.
[0005] The invention also provides a method for preparing low-temperature copper slurry that can be sintered in an atmospheric environment.
[0006] The innovation of the present invention is to reduce the use of reducing agents and additives, and to achieve the functions of reducing agents and additives at the same time through dispersant materials. The use of dispersants reduces the components necessary for copper slurry preparation, simplifies the process, and further reduces costs.
[0007] In order to achieve the above-mentioned object of the invention, the technical solution of the present invention is:
[0008] A low-temperature copper paste that can be sintered in an atmospheric environment, characterized in that it comprises the following raw materials in percentage by mass: 20-40% nano copper powder, 20-50% micron copper wire, 1-10% flake copper powder, 0.15-3% binder, 10-30% solvent, and 6.45-17% dispersant;
[0009] The binder is selected from one of ethyl cellulose, polyvinyl alcohol, polyvinyl butyral ester, hydroxyethyl cellulose, hydroxychloroacetic acid resin, and polyurethane;
[0010] The solvent is selected from one or two of ethylene glycol, dibasic acid ester, diethylene glycol butyl ether, diethylene glycol butyl ether acetate, isophorone, and dipropylene glycol formate;
[0011] The dispersant is selected from one of n-hexylamine, N,N-dimethyldecylamine, 3-aminopropionamide, silane coupling agent and N,N-diisopropylmethylamine.
[0012] Furthermore, the average particle size of the nano copper powder is 10 to 70 nm.
[0013] Furthermore, the average diameter of the micron copper wire is 0.2-1 μm, and the length is 1-10 μm.
[0014] A method for preparing a low-temperature copper slurry that can be sintered in an atmospheric environment, characterized in that it comprises the following steps:
[0015] (1) First, the binder is added to the solvent, and after heating and dissolving and stirring, a mixed solution is formed, and then the dispersant is added to the mixed solution, and finally the nano copper powder, micron copper wire and flaky copper powder are added to form a mixed slurry, and the viscosity of the mixed slurry is controlled to be 60 to 140 Pa·s;
[0016] (2) adding the mixed slurry of step (1) into a planetary mixer and stirring for 30 to 80 minutes for pre-dispersion to obtain a pre-dispersed mixed slurry;
[0017] (3) The pre-dispersed mixed slurry is added to a three-roll mill for secondary dispersion to finally obtain a low-temperature copper slurry.
[0018] Furthermore, the mass percentage content of the binder in the mixed slurry is 0.3-1.1%.
[0019] Furthermore, the mass percentage content of the nano copper powder in the mixed slurry is 25-35%.
[0020] Furthermore, the mass percentage of the micron copper wire in the mixed slurry is 28-38%.
[0021] The beneficial effects of the present invention are:
[0022] 1. The present invention innovatively reduces the use of reducing agents and additives, and achieves the effects of reducing agents and additives at the same time through dispersant materials. The dispersant is different from the commonly used dispersants, and is particularly selected from organic materials whose functional groups contain amino groups and amide groups. This material can not only play a dispersing role in coating copper particles to prevent agglomeration, but also can reduce oxidized copper powder, copper wire, and copper sheet by photothermal decomposition during photon sintering, thereby achieving the effect of reducing agent. Finally, this type of dispersant can play the role of a thickener by controlling the amount added and adjusting the viscosity. Therefore, the use of a dispersant in the present invention reduces the components necessary for the preparation of copper slurry, simplifies the process, and further reduces costs.
[0023] 2. The present invention innovatively uses micron copper wire. Since the conductive modes of copper particles in the copper paste are divided into contact conduction and tunneling conduction, contact conduction only requires the formation of sintering necks between copper particles to form a conductive path, and has very good conductivity; tunneling conduction requires a certain amount of excitation energy to make electrons jump from one side to the other side, the required energy is high, and the conductivity is poor; therefore, on the one hand, the micron copper wire itself does not need to form a sintering neck as a conductive path, which increases the conductivity while reducing the use of nano copper powder, further reducing costs; on the other hand, after adding the micron copper wire, by forming a "point-line-surface" conductive phase structure, the probability of copper particles being separated by resin is reduced, thereby reducing the probability of tunneling conduction, increasing the probability of contact conduction, and improving the conductivity of the low-temperature copper paste.
[0024] 3. The low-temperature copper paste prepared by the present invention is suitable for the photon sintering method, and the energy density applicable range is 2J / cm 2 ~7J / cm 2 Combined with this method, the energy density can be adjusted to form a sintering neck between copper powders without destroying the flexible substrate film, thereby achieving the purpose of low-temperature sintering. It is suitable for circuit printing, terminal electrodes and electronic component preparation in flexible devices.
[0025] 4. The low-temperature copper paste prepared by the present invention has good surface morphology. The resin material can form a substrate-resin-particle structure with copper particles, has good thixotropy, and has a smooth surface without protrusions after printing, which enhances the stability of the low-temperature copper paste and avoids micro-area stress concentration during use.
[0026] 4. The sintering time of the low-temperature copper paste prepared by the present invention is extremely short (≤1ms). Since the low-temperature copper paste prepared by the present invention is suitable for the photon sintering method, it relies on photons with high energy to irradiate the surface of the copper film layer, and converts the high energy of the photons into heat energy and transfers it to the copper powder, so that the copper powder can form a sintering neck within milliseconds, thereby completing sintering and greatly increasing the sintering efficiency.
[0027] 5. In the present invention, all raw materials are non-toxic and harmless, meeting the requirements of green production. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 These are SEM images of the film morphology before and after photon sintering of Example 1: (a) SEM image before sintering; (b) SEM image after sintering.
[0029] Figure 2 This is a 3D map of the surface roughness of the film layer after photon sintering in Example 1. DETAILED DESCRIPTION
[0030] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the accompanying drawings.
[0031] Embodiment 1: A low-temperature copper paste that can be sintered in an atmospheric environment comprises the following raw materials in percentage by mass: 40% nano copper powder, 20% micron copper wire, 10% flaky copper powder, 0.15-3% binder, 10-30% solvent, and 6.45-17% dispersant; the average particle size of the nano copper powder is 10-70 nm, the average diameter of the micron copper wire is 0.2-1 μm, and the length is 1-10 μm.
[0032] The binder is polyvinyl butyral ester; the solvent is dibasic acid ester; and the dispersant is n-hexylamine.
[0033] The preparation method is as follows:
[0034] (1) First, the binder is added to the solvent, and after heating and dissolving and stirring, a mixed solution is formed, and then the dispersant is added to the mixed solution, and finally the nano copper powder, micron copper wire and flaky copper powder are added to form a mixed slurry, and the viscosity of the mixed slurry is controlled to be 98.5 Pa·s;
[0035] (2) adding the mixed slurry of step (1) into a planetary mixer and stirring for 50 minutes for pre-dispersion to obtain a pre-dispersed mixed slurry;
[0036] (3) The pre-dispersed mixed slurry is added to a three-roll mill for secondary dispersion to finally obtain a low-temperature copper slurry.
[0037] Example 2-Example 6, refer to Example 1, the raw material composition and process parameters of each example are shown in the following table
[0038]
[0039]
[0040] The properties of the conductive copper paste of Example 1-6 after photon sintering and curing are as follows:
[0041] Example Square resistance (μΩ / □) Antioxidant Sintering temperature(℃) Example 1 348 No change for 130 days 180 Example 2 482 No change for 130 days 180 Example 3 256 No change for 130 days 180 Example 4 287 No change for 130 days 180 Example 5 405 No change for 130 days 180 Example 6 321 No change for 130 days 180
[0042] Embodiment 7: The binder is selected from one of ethyl cellulose, polyvinyl alcohol, polyvinyl butyral ester, hydroxyethyl cellulose, hydroxychloroacetic acid resin, and polyurethane; the solvent is selected from one or two of ethylene glycol, dibasic ester, diethylene glycol butyl ether, diethylene glycol butyl ether acetate, isophorone, and dipropylene glycol formate; the dispersant is selected from one of n-hexylamine, N,N-dimethyldecylamine, 3-aminopropionamide, silane coupling agent, and N,N-diisopropylmethylamine.
[0043] Comparative Example 1: The conductive copper paste was prepared by the method of Example 1 of CN117497223A, as follows:
[0044] A conductive copper paste comprises the following components in percentage by weight: 85% conductive phase, 15% organic phase (including 1.5% functional phase, 3% reducing agent phase, 1.5% resin phase, 9% solvent phase). Functional additives, organic resin, and reducing agent are placed in an organic solvent and fully dissolved at a certain temperature to form a mixed solution, and then a copper-containing composition is added to the mixed solution, and the mixture is mixed and stirred in a planetary mixer at 1200 rpm for 90 seconds, and rolled after stirring to obtain a copper paste.
[0045] In the above preparation method, the organic phase added to the reference example 1 contains a reducing agent, an auxiliary agent, a functional additive, etc., and the process is complicated. Secondly, the resistivity of the copper paste in the reference example 1 after photon sintering is converted into a square resistance of 565μΩ / □, which is greater than the maximum square resistance in the embodiment of the present invention. Finally, the characteristics of oxidation resistance and rough surface morphology are not reflected in the reference example 1. Examples 1 to 6 of the present invention only include two steps of mixing and dispersing, and the components only include copper powder, a binding phase, a solvent and a dispersant. The purity of the copper powder is ensured by the reduction effect of photon sintering. The process is simple, the energy consumption is lower, and better effects are achieved by reducing the components. In addition, the copper paste of the present invention can be photon sintered in an atmospheric environment and can be applied to a flexible substrate.
[0046] Comparative Example 2: Conductive copper paste was prepared by the method of Example 1 of CN118098674A, as follows:
[0047] 5% of chloroacetic acid resin, 25% of methyl nylonate, and 0.5wt% of BYK-111 dispersant by powder mass are fully mixed to obtain a resin system, and 50% of 50nm nano copper powder, 15% of 1μm spherical micron copper powder, and 5% of 10μm flaky copper powder and the resin system are mixed in a high-speed mixer (mixed at a speed of 1500rpm / min for 90s, mixed at a speed of 2500rpm / min for 60s, and mixed at a speed of 1000rpm / min for 30s) and a three-roll grinder (the gap between the front rollers is 20μm, and the gap between the rear rollers is 30μm) to obtain a photon sintering conductive copper slurry.
[0048] In the above preparation method, the control example 2 uses 50% nano copper powder, which is higher than the maximum amount of nano copper powder used in the present invention, and the cost is higher; secondly, although the control example 2 only contains a conductive phase, a bonding phase, a solvent and an additive, it does not indicate that the additive has an antioxidant effect, and does not indicate the resistance value and the surface morphology of the film layer, which is crucial for the application of copper paste. Finally, the sintering time of the copper paste suitable for photon sintering in the control example 2 is only ≤1s. In contrast, the sintering time of the present invention only needs 1800μm (1.8ms) to obtain a sintered film layer with a maximum square resistance of 482mΩ / □, with a short sintering time, a smooth film surface and a good conductive effect.
[0049] Comparative Example 3: Conductive copper paste was prepared by the method of Example 4 of CN115642000B, as follows:
[0050] The invention discloses a method for preparing a conductive copper paste capable of photon sintering. The raw material composition of the conductive copper paste is as follows in terms of mass percentage: 0.25% of micron copper powder with an average particle size of 0.2-1 μm, 80% of nano copper powder with an average particle size of 30-90 nm, 3.55% of flaky copper powder with an average particle size of 1-50 μm, 1.2% of a binder polyvinyl alcohol, 9% of a solvent dibasic acid ester, 5% of a reducing agent octadecylamine, 1% of an auxiliary silicone resin, and 1% of bisphenol A.
[0051] In the above-mentioned photon sintering copper slurry preparation method, the content of nano copper powder used in Reference Example 3 reached 80%, and the cost increased significantly. The maximum amount of nano copper powder used in the present invention is only 40%. Secondly, no dispersant was added in Reference Example 3, and the copper powder, especially the nano copper powder, could not be evenly dispersed, resulting in the agglomeration of the copper powder. After sintering, the film performance dropped significantly and the square resistance increased. It can be seen here that the minimum resistance value of Reference Example 3 is two orders of magnitude larger than the resistance value of the present invention. Finally, in addition to the conductive phase, the adhesive phase and the solvent, Reference Example 3 also contains a reducing agent and an auxiliary agent, the process is complicated, and the surface morphology is not described. In contrast, the present invention achieves better results while simplifying the process and reducing costs by reducing the components.
[0052] The described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
Claims
1. A low-temperature copper paste that can be sintered in an atmospheric environment, characterized in that: The raw materials include the following mass percentages: 20-40% nano copper powder, 20-50% micron copper wire, 1-10% flake copper powder, 0.15-3% binder, 10-30% solvent, and 6.45-17% dispersant; The binder is selected from one of ethyl cellulose, polyvinyl alcohol, polyvinyl butyral ester, hydroxyethyl cellulose, hydroxychloroacetic acid resin, and polyurethane; The solvent is selected from one or two of ethylene glycol, dibasic acid ester, diethylene glycol butyl ether, diethylene glycol butyl ether acetate, isophorone, and dipropylene glycol formate; The dispersant is selected from one of n-hexylamine, N,N-dimethyldecylamine, 3-aminopropionamide, silane coupling agent and N,N-diisopropylmethylamine.
2. The method for preparing low-temperature copper paste that can be sintered under atmospheric environment according to claim 1, characterized in that: The average particle size of the nano copper powder is 10-70 nm.
3. The method for preparing low-temperature copper paste that can be sintered under atmospheric environment according to claim 1, characterized in that: The average diameter of the micron copper wire is 0.2-1 μm, and the length is 1-10 μm.
4. A method for preparing a low-temperature copper paste that can be sintered in an atmospheric environment, characterized in that: The following steps are involved: (1) First, the binder is added to the solvent, and after heating and dissolving and stirring, a mixed solution is formed, and then the dispersant is added to the mixed solution, and finally the nano copper powder, micron copper wire and flaky copper powder are added to form a mixed slurry, and the viscosity of the mixed slurry is controlled to be 60-140 Pa·s; (2) adding the mixed slurry of step (1) into a planetary mixer and stirring for 30 to 80 minutes for pre-dispersion to obtain a pre-dispersed mixed slurry; (3) The pre-dispersed mixed slurry is added to a three-roll mill for secondary dispersion to finally obtain a low-temperature copper slurry.
5. The method for preparing low-temperature copper paste sintered under atmospheric environment according to claim 4, characterized in that: The mass percentage content of the binder in the mixed slurry is 0.3-1.1%.
6. The method for preparing low-temperature copper paste sintered under atmospheric environment according to claim 4, characterized in that: The mass percentage content of the nano copper powder in the mixed slurry is 25-35%.
7. The method for preparing low-temperature copper paste sintered under atmospheric environment according to claim 4, characterized in that: The mass percentage of the micron copper wire in the mixed slurry is 28-38%.
Citation Information
Patent Citations
A method for preparing photonic sinterable conductive copper paste
CN115642000B
Copper paste, copper circuit, flexible electronic device and photovoltaic heterojunction cell
CN117497223A
Photon sintering conductive copper paste and preparation method thereof, antenna and RFID tag
CN118098674A